Infectivity and Persistence of Steinernema scapterisci Nematodes on Pasture Mole Crickets in Florida - J. Howard Frank; Martin B. Adjei; G. C. Smart, Jr.; B. J. Adams (EDIS, 2006)
Revised! With the 25 year long formal UF/IFAS Mole Cricket Research Program ended in fall 2004, the authors have revised this 2002 publication which reported results of the ongoing research, to provide an account of the experience of UF/IFAS personnel and collaborators in the Florida Department of Consumer Services in this successful program. Includes references. Published by the UF Department of Entomology and Nematology, October 2006.